The Existence of Secondary School Education through the Role of the Principal: Case Study at SMA Negeri 13 Surabaya - Sa’adah, Ummi; Putra, Briyan Cadalora (Formosa Journal of Applied Sciences, 2024)
This study is a qualitative study with a descriptive approach. The objectives of this study are: 1) To describe the role of the principal in designing, organizing, implementing, supervising and evaluating to maintain the Existence of Education through the Management of Senior High Schools at SMA Negeri 13 Surabaya, 2) To explain the Impact of the Principal's Role in designing, organizing, implementing, supervising and evaluating to maintain the Existence of Education through School Management at SMA Negeri 13 Surabaya. The research instrument consists of two instruments, namely the key instrument and the supporting instrument. The key instrument in this study while the supporting instrument in this study are teachers, students, parents of students.